Determinants of Online Dating Application Among Millennials - Jamaludin, Norlelawati; Mohd Yusof, Nuryusmawati; Maishahadi, Faizah; Sohid, Faizah; Syed Omar, Syed Asherene Syed; Ishak, Mohd Fikri; Syed Yusof, Syed Mustaqim; Saidon, Janiffa (Information Management and Business Review, 2024)
Online dating has become increasingly popular in recent years, these platforms provide a convenient and accessible way to meet new people. Studies on the use of dating applications among men and women highlight how these technologies shape communication practices and social relationships. For this study, the Unified Theory of Acceptance and Use of Technology (UTAUT) was applied to discover the determinants of online dating apps’ adoption intention. Possible determinants that might affect the intention to adopt online dating apps are sought and critically reviewed. The variables proposed in this research include performance expectancy, effort expectancy, social influence, facilitating conditions, and an additional variable – trust. Five hypotheses were constructed, questionnaires were distributed and responses were collected to determine the adoption intention of young millennials in Malaysia. The test results indicated that trust, performance expectancy and social influence influenced the adoption intention of online dating applications. Based on the results, for performance expectancy, it was revealed that users expressed concerns about the utility of dating applications in facilitating beneficial functions, such as broadening social networks, enhancing dating opportunities, and meeting dating needs. For social influence, it revealed that individuals, especially peers, who hold significance in their lives, influence their decision to engage with online dating apps. These influential individuals impact the users’ intentions by communicating the benefits of online dating apps and recommending their use. As trust improves, millennials are less reluctant to adopt online dating apps, contributing to an increase in the user base for such applications